PENGEMBANGAN MEDIA LADDER BOARD BERBASIS PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SEKOLAH DASAR - Amelia Rahma Juwita; Yustia Suntari; Chrisnaji Banindra Yudha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the low reading comprehension skills of elementary school students, particularly in understanding texts, answering questions, and drawing conclusions. Learning activities that are still dominated by textbooks and conventional methods also make students less engaged and easily bored. This study aims to analyze the needs of teachers and students regarding the development of Ladder Board learning media based on Problem Based Learning (PBL) to improve the reading comprehension skills of fourth-grade elementary school students. This research uses the Research and Development (R&D) method, focusing on the first stage of the ADDIE model, namely the analysis phase. The participants consisted of 28 fourth-grade students and one homeroom teacher at SDN Pademangan Timur 01. Data were collected through student needs questionnaires, interviews with teachers, and initial classroom observation. The data were analyzed using the Respondent Achievement Level (RAL) formula and descriptive qualitative analysis. The results showed that 75% of students experienced difficulties in understanding reading texts and 79% had difficulties in drawing conclusions. In addition, 79% of students felt bored with textbook-based learning, while 84%–93% showed high interest in game-based learning. Interview and observation results also confirmed that the current learning media has not optimally supported students’ comprehension skills. In conclusion, this study identifies the need for the development of more enjoyable and structured learning media. Therefore, the Ladder Board media is expected to become a solution to gradually and pleasantly improve students’ reading comprehension skills.